Detection of glyphosate residues in feed, saliva, urine and faeces from a cattle farm: a pilot study. Issue 7 (3rd July 2022) - Feltracco, Matteo; Barbaro, Elena; Scopel, Monica; Piazza, Rossano; Barbante, Carlo; Gambaro, Andrea
Abstract: Forty-two samples of feed, saliva, urines, and faeces collected from a cattle farm were investigated with the aim to evaluate the occurrence of glyphosate in faeces, urine and saliva. Glyphosate in the feed was also quantified to understand how it was assimilated by mammals. All cows excreted glyphosate in their faeces at concentrations between 57 and 983 ng g −1 . In contrast, only 55% of urine and one sample of saliva tested positive. Most of the feeds demonstrated a non-negligible presence of glyphosate. In particular, a silage containing soybeans from genetically modified cultivation showed a concentration one order of magnitude higher than the other feeds. This study aims to provide the first complete determination of glyphosate in a cattle farm, considering the possible re-entry into the environment through the spreading of liquid and solid sewage and its possible impact on groundwater. Graphical Abstract: UF0001